Hadiths About Human Intellect in the Book of Shu'ab al Iman by Imam al-Baihaqi - Adnir, Farid; Yuslem, Nawir; Nasution, Muhammad Roihan (Journal International Dakwah and Communication, 2024)
This article discusses the hadith contained in the book "Syu'ab al-Iman by Imam al Baihaqi, which emphasizes the importance of Islam directing the potential of the human mind at an early stage, analyzing the wisdom of Allah SWT, and absorbing it, which is something that is very close to the ruler spirit, namely Allah, the Almighty Creator, the Almighty, who created the heavens and the earth correctly. The aim of this research is to analyze the hadith concept about human reason in the book Syu'ab al-Iman by Imam Baihaqi. This research was carried out using literature research, namely reading, analyzing through books, journals, articles, and using a hadith science approach, namely thematic. The research results show that the hadith on human reason contained in the book Syu'ab al-Iman by Imam al-Baihaqi conveys the message that understanding the basics of one's reason is the key to truly appreciating Islamic teachings. The context of the hadith details how the development of reason and critical thinking are important aspects in understanding and deeply appreciating Islamic values. This hadith also highlights the concept that Islam does not only demand outward obedience, but also teaches the necessity to understand and use reason as the basis of religion. By detailing the hadith in the book "Syu'ab al-Iman", readers are invited to reflect on how mature reason can provide a deeper dimension to one's Islamic practice.